Enhancing the of Performance of Lithium‐Sulfur Batteries through Electrochemical Impregnation of Sulfur in Hierarchical Mesoporous Carbon Nanoparticles. Issue 17 (9th September 2020) - Kim, Seong‐Jun; Ahn, Minchul; Park, Jungjin; Jeoun, Yunseo; Yu, Seung‐Ho; Min, Dal‐Hee; Sung, Yung‐Eun
Abstract: Hierarchical mesoporous carbon was studied as a key material for enhancing sulfur utilization in Li−S batteries. Commonly, thermal sulfur infiltration into mesoporous carbon was a representative method for S−C composites; however, these had some problems such as pore blocking or nonuniform deposition of sulfur. Electrochemical sulfur impregnation without chemical or thermal infiltration reduced the preprocess time and enabled efficient polysulfide diffusion into the carbon pores. As the soluble polysulfides are smaller and more mobile than solid‐state sulfur, they could be physically or chemically adsorbed into the pores of the carbon additives. This approach enhanced the cycle stability and rate performance of the batteries. This study will provide an efficient and economic use of porous carbons in the Li−S battery field. Abstract : Missing the meltdown : Simple electrochemical impregnation for the accommodation of sulfur in mesoporous carbon provides enhanced battery performance. This approach suggests an alternative to melt diffusion method of sulfur.